Proximal Aortic Dissection: A Diagnostic Challenge in a Condition When Minutes Count, a Systematic Review - Tiosso Batistetti, Vitor; Levin, Ricardo (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Background: Proximal aortic dissection is characterized by the formation of a false lumen in the medial layer of the aortic wall. This pathology has an incremental risk of death of 1-2% for each hour since the onset of symptoms. Despite notable advances in diagnostic tools, early diagnosis of this pathology remains a challenge. Material and methods: A systematic review of published studies on acute aortic dissection was performed with a focus on factors associated with a delay in diagnosis and early treatment. Results: The search yielded 16 articles where patient, diagnostic, and treatment availability factors were identified. Among the most relevant factors are the female sex, atypical symptoms, suspicion of coronary disease, and the initial presentation in tertiary care hospitals. Conclusion: The main findings of this systematic review were numerous variables that are associated with a delay in diagnosis and treatment, including patient factors, level of diagnostic suspicion, diagnostic methods used, and level of complexity of the receiving medical center